File Sharing. - Rothkopf, Scott (Artforum International, 2012)
The article discusses "Untitled," a 2006 artwork by the artist Kelley Walker. The work is based on a piece made by the artist in 2003 titled "schema; Aquafresh plus Crest with whitener," a digital image created via the use of a scanner and the digital imaging software Photoshop. "Untitled" was the result of the artist taking an image of "schema" which appeared on the cover of the periodical "Artforum" and manipulating it to produce a glowing light box.